2017
DOI: 10.31231/osf.io/evcga
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural plasticity of the social brain: Differential change after socio-affective and cognitive mental training

Abstract: Although neuroscientific research has revealed experience-dependent brain changes across the life span in sensory, motor, and cognitive domains, plasticity relating to social capacities remains largely unknown. To investigate whether the targeted mental training of different cognitive and social skills can induce specific changes in brain morphology, we collected longitudinal magnetic resonance imaging (MRI) data throughout a 9-month mental training intervention from a large sample of adults between 20 and 55 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 83 publications
7
48
1
4
Order By: Relevance
“…For example, factors that may influence the health status for low-SES individuals may not have the same impact for high-SES individuals, such as living conditions or adequate nutrition (Adler et al 1994). Part of the intermediate network, SMG structure was found to be altered after nine months of cognitive mental training on tasks related to mindfulness, perspective-taking, and emotion (Valk et al, 2017). These structural plasticity findings in the SMG suggest sensitivity to changes in one's social experience.…”
Section: Discussionmentioning
confidence: 99%
“…For example, factors that may influence the health status for low-SES individuals may not have the same impact for high-SES individuals, such as living conditions or adequate nutrition (Adler et al 1994). Part of the intermediate network, SMG structure was found to be altered after nine months of cognitive mental training on tasks related to mindfulness, perspective-taking, and emotion (Valk et al, 2017). These structural plasticity findings in the SMG suggest sensitivity to changes in one's social experience.…”
Section: Discussionmentioning
confidence: 99%
“…At no point did the authors discuss the criteria for choosing the compassion focused intervention in contrast to a mindfulness intervention other than a keyword search. Indeed, as noted previously, there are notable and important physiological differences in mindfulness versus compassion training (Valk et al, 2017). Many of their keywords did not actually include compassion (e.g., dialectical behaviour therapy).…”
Section: Heterogeneity and Classification Of The 'Self-compassion Thementioning
confidence: 93%
“…Matos et al, (2017) found that practising compassionate mind skills for two weeks resulted in a range of beneficial psychological changes, reduced fears of compassion and was associated with well-being and changes in heart rate variability. Compassion focused therapy (CFT) and compassionate mind training (CMT) are designed to tap into the physiological and neurobiological systems that underpin evolved caring mechanisms (Gilbert, 2014(Gilbert, , 2017b; hence why changes in heart rate variability (Kirby, Doty, Petrocchi, & Gilbert, Matos et al, 2016) and neurobiological changes associated with training (Vrtička, et al 2017;Valk et al, 2017;Weng et al, 2018) are of interest.…”
Section: Setting the Backgroundmentioning
confidence: 99%
See 2 more Smart Citations